An Assessment of Alternative Energy Storage Systems in Saudi Arabia - Alzhrani, Abdoalateef (Engineering, Technology & Applied Science Research, 2026)
This study investigates the suitability of non-battery Energy Storage Systems (ESS) for large-scale deployment in Saudi Arabia, with a focus on Flywheel Energy Storage Systems (FESS), Pumped Hydro Energy Storage (PHES), Compressed Air Energy Storage (CAES), and Gravity Energy Storage Systems (GESS) across their principal configurations. The analysis is framed within the Kingdom’s Vision 2030 objective of achieving 50% electricity generation from renewable sources and integrates regional electricity demand patterns for 2023 alongside climatic and geological considerations. A structured Multi-Criteria Decision-Making (MCDM) framework was developed, incorporating sixteen technical, environmental, operational, and economic criteria. The technological performance was assessed using both the Weighted Sum Model (WSM) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Consistency between the two methods, supported by sensitivity analysis of the most influential criteria, demonstrates the robustness of the evaluation. Results show that national summer peak demand reaches approximately 70 GW. The Central and Eastern regions contribute 22.4 GW and 20.9 GW, respectively, highlighting favorable conditions for FESS due to its rapid response and grid-support capabilities. The southwestern region, particularly Asir, exhibits strong suitability for PHES owing to its elevation profile and existing dam infrastructure, whereas GESS aligns well with Saudi Arabia’s extensive flat terrain and proximity to large-scale solar developments. The study concludes that non-battery ESS technologies, when matched to regional characteristics and infrastructure, represent technically viable and strategically valuable solutions for enhancing grid flexibility and supporting renewable integration in Saudi Arabia.